Perancangan Aplikasi Steganografi Dengan Teknik LSB dan AlgoritmaRC4 & Base64 Encoding - Soleh, Oleh; Alfiah, Fifit; Yusuf, Budi (Technomedia Journal, 2018)
The concealment of secret messages by inserting messages into an image file or more commonly known as steganography is the development of cryptography. This hidden secret message with steganography does not attract attention because the message is simply inserted into a file. Many methods are used to hide messages with steganography. Some methods of steganographic algorithms use a combination to perform the task of concealment of secret messages. From the existing method, of course has its own shortcomings and advantages. The method used is LSB (Least Significant Bit) method, RC4 algorithm and Encoding Base64. This method combines cryptographic techniques with steganography techniques. The message is encrypted before it is inserted into a file. Implementation of this method can later help users to send messages safely without being noticed by others.